PEMODELAN TARIKAN PERJALANAN MENUJU PUSAT PERBELANJAAN DI KABUPATEN BADUNG, PROVINSI BALI - Suthanaya, Putu Alit (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010, 2012)
Badung Regency, especially South of Badung is the center of tourism in Bali where development of shopping centers increases. The existence of these shopping centers as one of commercial facilities has attracted trips which cause the increase of traffic volume, degree of saturation, and conflict between through and local traffic. Therefore, a study on the amount of trips attracted to these shopping centers is required. The objectives of this study are to evaluate trips mode composition and to model trip attraction to shopping centers. The primary data were obtained from trip attraction survey whilst the secondary data were obtained from the administration of the shopping centers (i.e. total area, floor area, parking area, number of employments, and number of supporting facilities available). The results of analyses on customer mode split indicated that the proportion of using motor bike was 58,43%, 41,37% light vehicle, 0,10% heavy vehicle and 0,10% unmotorised vehicle. Multiple regression analyses indicated that independent variables that influence trip attraction on peak hour are total area (X1) and parking area (X2). For one day trips, only total area had a significant influence. Trip attraction model for morning peak hour, evening peak hour ad for one day trips are: Y11 = 105,747 + 0,005 .X1 (R2 = 0,967); Y12 = 45,601 + 0,015 .X3 (R2 = 0,984); Y13 = 3405,73 + 0,187. X1 (R2 = 0,920), respectively.
Keywords: trip attraction, shopping centers